APLIKASI TECHNOLOGY ACCEPTANCE MODEL PADA SISTEM INFORMASI MANAJEMEN RUMAH SAKIT DI RUMAH SAKIT ORTOPEDI PROF. DR. R. SOEHARSO SURAKARTA - Supriyanti Supriyanti; Muhammad Cholil (Universitas Muhammadiyah Surakarta, 2016)
The purpose of this study to apply the Technology Acceptance Model (TAM) on theHospital Management Information System. This research is important because changesin hospital management information system (SIMRS) of the old system in collaborationwith third parties to the new system is a standalone system that was developed by the ITteam RSO Prof. dr. R. Soeharso requires a process of transition, which for some employeeslead to conflict in the process of adaptation. This study is an empirical research withquantitative methods. The population of all employees who use information managementsystem as much as 382 people, 193 people sampled with sample random samplingtechnique. The results of this study include shows, computer selt efficacy influence theperceived usefulness and perceived ease of use of technology in hospital managementinformation system. Subjective norms affect the perceived usefulness and perceived easeof use of technology in hospital management information system. System accessibilitywhile no effect on the perception of the benefits, but the effect on the perceived ease ofuse of technology in hospital management information system.